Stink and the Great Guinea Pig Express [Smraďo anglicky] / Book 4. - McDonald, Megan (Walker Books Ltd, 2020)
Meet Judy Moody's brother!GUINEA PIGS A-GO-GO!When three guinea pigs from the local pet shop make a great escape, Stink Moody and his friends Webster and Sophie spring into action. Ta-da! The Fantastic Fur Friends round up the little hairballs and bring them safely back to Mrs. Birdwistle’s shop, where they discover oohla- la! guinea pig pandemonium! Time for the Great Guinea Pig Giveaway! Stink and company hit the road aboard the Squeals on Wheels Express in a crazy quest to fi nd good homes for 101 squealing, whistling, chirping, wiggly piggies. FUR-eaky!